Efficacy and safety of valsartan compared with enalapril at different altitudes (2000)
To compare the safety, tolerability, and antihypertensive efficacy of valsartan with enalapril at different altitudes. A total of 142 adult Colombian outpatients with mild to moderate essential hypertension were recruited in 3 cities at different altitudes (Bogotá at 2600 m, Medellı́n at 1538 m and Barranquilla at 100 m) and randomized in an open label fashion to receive either valsartan 80 mg once daily or enalapril 20 mg once daily for 8 weeks. Those patients not responding at 4 weeks received additional 1.25 mg indapamide daily during the remaining trial period. The primary efficacy variable was the change in mean sitting diastolic blood pressure (SDBP) from baseline to 4 weeks. Secondary efficacy variables included the change in mean sitting systolic blood pressure (SSBP). The primary criterion for tolerability was the incidence of adverse experiences. Both valsartan and enalapril reduced mean SDBP and SSBP with similar efficacy, independent of altitude. Adverse events irrespective of relationship to trial drug were reported by 12 patients (18.8%) on valsartan and by 15 (23.4%) patients on enalapril. Enalapril was associated with a significantly (P<0.05) higher rate of dry cough and more cases of headache than valsartan. Valsartan 80 mg once daily is as effective as enalapril 20 mg once daily in reducing blood pressure, with tolerability profile at least as good as enalapril’s.